2022
DOI: 10.3389/fmicb.2022.987756
|View full text |Cite
|
Sign up to set email alerts
|

MliR, a novel MerR-like regulator of iron homeostasis, impacts metabolism, membrane remodeling, and cell adhesion in the marine Bacteroidetes Bizionia argentinensis

Abstract: The MerR family is a group of transcriptional activators with conserved N-terminal helix-turn-helix DNA binding domains and variable C-terminal effector binding regions. In most MerR proteins the effector binding domain (EBD) contains a cysteine center suited for metal binding and mediates the response to environmental stimuli, such as oxidative stress, heavy metals or antibiotics. We here present a novel transcriptional regulator classified in the MerR superfamily that lacks an EBD domain and has neither cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…There are two MerR transcriptional regulators (G2EA47, G2E8Y3); they both have an HTH merR‐type domain in the N‐terminal region, but they do not have the copper‐binding site reported for E. coli CueR (Changela et al, 2003 ), so they may not be involved in the regulation of copper homeostasis. Indeed, recently, it was reported that one of these transcriptional regulators is involved in iron homeostasis (Pellizza et al, 2022 ). Three BlaI/MecI/CopY family transcriptional regulators with similarity to the transcriptional repressor CopY from Enterococcus hirae (Q47839) were found in the genome of B. argentinensis (G2EAK1, G2ED45 and G2EAI2), but none of them has conserved the CopY copper‐binding site.…”
Section: Resultsmentioning
confidence: 99%
“…There are two MerR transcriptional regulators (G2EA47, G2E8Y3); they both have an HTH merR‐type domain in the N‐terminal region, but they do not have the copper‐binding site reported for E. coli CueR (Changela et al, 2003 ), so they may not be involved in the regulation of copper homeostasis. Indeed, recently, it was reported that one of these transcriptional regulators is involved in iron homeostasis (Pellizza et al, 2022 ). Three BlaI/MecI/CopY family transcriptional regulators with similarity to the transcriptional repressor CopY from Enterococcus hirae (Q47839) were found in the genome of B. argentinensis (G2EAK1, G2ED45 and G2EAI2), but none of them has conserved the CopY copper‐binding site.…”
Section: Resultsmentioning
confidence: 99%